2017
DOI: 10.1002/2016jb013096
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric structure of the southeastern margin of the Tibetan Plateau from Rayleigh wave tomography

Abstract: Lithospheric shear wave velocity beneath the southeastern margin of the Tibetan Plateau is obtained from Rayleigh wave tomography using earthquake data recorded by the temporary ChinArray and permanent China Digital Seismic Array. Fundamental mode Rayleigh wave phase velocities at periods of 20–100 s are determined and used to construct the 3‐D shear wave velocity model. Low‐velocity anomalies appear along or close to the major faults in the middle crust and become a broad zone in the lower crust, suggesting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Many geophysical studies (Bao et al, ; Bao, Sun, et al, ; Fu et al, ; Jiang et al, ; Lei et al, ; J. Li et al, ; X. Liang et al, , ; Q. Y. Liu et al, ; Tian et al, ; C. Wang et al, ; X. Wang et al, ; Xu et al, ; Yao et al, , ; Yu & Chen, ; X. Zhang et al, ; Zhou & Lei, ) explored evidence supporting one or more of the aforementioned models. However, views on the development of the Tibetan Plateau are diverse and often exclusive of one another or of opposing schools of thought.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many geophysical studies (Bao et al, ; Bao, Sun, et al, ; Fu et al, ; Jiang et al, ; Lei et al, ; J. Li et al, ; X. Liang et al, , ; Q. Y. Liu et al, ; Tian et al, ; C. Wang et al, ; X. Wang et al, ; Xu et al, ; Yao et al, , ; Yu & Chen, ; X. Zhang et al, ; Zhou & Lei, ) explored evidence supporting one or more of the aforementioned models. However, views on the development of the Tibetan Plateau are diverse and often exclusive of one another or of opposing schools of thought.…”
Section: Introductionmentioning
confidence: 99%
“…Many geophysical studies (Bao et al, 2013;Bao, Sun, et al, 2015;Fu et al, 2017;Jiang et al, 2014;Lei et al, 2014;J. Li et al, 2011;X.…”
Section: Introductionmentioning
confidence: 99%
“…Our tomographic images reveal widespread low SH wave velocity zones (Figures a–c and ) in the crust beneath the NE Tibetan plateau, specifically in the QOB and SGT regions. Such slow V SH is also observed in the lower crust of the southeastern Tibetan plateau (Fu et al, ), which is interpreted as an indicator of lower crustal flow. SV wave velocity obtained from Rayleigh wave ambient noise tomography indicated that the midlower crustal low velocity zones distribute across most of the Tibetan plateau (Jiang et al, ; Li et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…Specifically, the model of lower crustal flow explains the crustal thickening in the Tibetan margin well and has been supported by geophysical results in recent years, including high‐conductivity anomalies (e.g., Bai et al, 2010), low‐velocity anomalies (e.g., Bao et al, 2015; M. Chen et al, 2014; Fu et al, 2017; Z. Huang et al, 2018; Liu et al, 2014; W. Wang et al, 2014; Wei et al, 2013; Yao et al, 2008, 2010), and positive radial anisotropies ( V SH > V SV ) (H. Huang et al, 2010; Xie et al, 2017) and by GPS measurements (Shen et al, 2005). Previous receiver function studies have shown a gentle variation in the Moho topography from the Tibetan Plateau to the Yangtze Craton (e.g., Sun et al, 2012; W. Wang et al, 2017; X. Xu et al, 2013), consistent with the Moho variation predicted by the lower crustal flow model.…”
Section: Introductionmentioning
confidence: 63%
“…The crust of Tibet is thicker than that of the Yangtze Craton (Liu et al, 2014), and there is an abrupt Moho variation across the gradient zone. Relatively high velocity anomalies (Bao et al, 2015; M. Chen et al, 2014; Fu et al, 2017; Z. Huang et al, 2018; Wei et al, 2013; Yao et al, 2008) and negative radial anisotropy ( V SH < V SV ) (Xie et al, 2017) in the lower crust have been detected in the northern region of the Dianzhong subblock (Figure 10), suggesting a rigid deep crust in this region. Thus, the sharp Moho gradient across the Tibetan margin should result from the rheological contrast in the lower crust, that is, weak lower crust beneath Tibet and strong lower crust beneath the foreland of the Yangtze Craton (Dianzhong subblock).…”
Section: Discussionmentioning
confidence: 99%